Preparation of polyvinyl alcohol spinning fiber adsorbent and method for targeted lithium extraction from lithium-containing wastewater

By modifying polyvinyl alcohol and using electrospinning technology to prepare fiber adsorbents, the existing lithium adsorbents have been solved, and efficient and economical lithium ion recovery effect has been achieved.

CN119368151BActive Publication Date: 2025-03-21常州中源技术股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411899593.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing lithium adsorbents have problems such as poor selectivity, low adsorption capacity, poor stability, and difficult to prepare in large quantities.

Method used

Modified polyvinyl alcohol by ethylenediamine and divinylketone, a modified polyvinyl alcohol solution with enhanced adsorption properties is formed, and a fiber adsorbent is prepared by electrospinning technology.

Benefits of technology

It improves the selective recovery and adsorption capacity of lithium ions, enhances the durability and reusability of adsorbents, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368151B_ABST
    Figure CN119368151B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium adsorption, and in particular to a preparation method of a polyvinyl alcohol spinning fiber adsorbent and a method for targeted lithium extraction from lithium-containing wastewater. The invention uses industrial batch production to prepare the polyvinyl alcohol spinning fiber adsorbent by polymerization of polyvinyl alcohol and diketene; the polyvinyl alcohol spinning fiber has a large specific surface area, and many adsorption sites are exposed on the surface, which is conducive to the completion of adsorption; the synthesized polyvinyl alcohol spinning fiber adsorbent can be used for targeted removal of lithium ions in a solution, and the adsorption capacity of lithium ions can reach up to 29.2 mg / g, which is 3.6 to 7.4 times that of a general commercial resin adsorbent; the diketone-containing polymer adsorbent can realize efficient selective separation and recovery of lithium ions in a mixed solution of nickel, cobalt, manganese, magnesium, calcium and other ions; at the same time, the excellent stable structure of the spinning fiber makes it have good reusability, which is a great breakthrough in industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium adsorbent preparation, and in particular to a method for preparing a polyvinyl alcohol spinning fiber adsorbent and extracting lithium from lithium-containing wastewater in a targeted manner. Background Art

[0002] At present, the industrial resource recovery and treatment technologies for lithium waste liquid / wastewater mainly include: solvent extraction, membrane separation, electrochemical method, adsorption method, etc. The main factors affecting the selection of lithium extraction methods are the practicality of the method, the coexisting pollutant multivalent ions (i.e., Mg / Li mass ratio), and other coexisting competing ions (such as Na + , K + ) is affected. The pretreatment process for removing coexisting ions is complicated and time-consuming. Solvent extraction is currently the mainstream method for lithium extraction, and the supporting wet process is relatively complete. Extractants such as P204 and P507 have been commercialized. Their versatility can realize the comprehensive utilization of multiple resources in brine and wastewater. However, the disadvantages of extractants for lithium extraction are relatively obvious, including poor lithium selectivity, cumbersome and complex supporting process design, and large amounts of residual liquids such as hydrochloric acid are highly corrosive to equipment and difficult to handle. Electrochemical lithium capture systems such as electrochemical capacitive deionization and electrodialysis rely on external electric fields, and have problems of high cost and high energy consumption. Membrane-based lithium recovery technologies include membrane capacitive deionization, selective electrodialysis, nanofiltration (NF), ion imprinted membrane (IIM) and membrane distillation crystallization (MDC), which are driven by external stimuli such as thermal gradients, pressure and electric fields. These technologies have great development potential in the next-generation roadmap, but difficulties in energy consumption, separation efficiency and membrane durability limit their industrialization. Compared with other lithium extraction processes, the adsorption method is suitable for recovering lithium from low-grade lithium-containing salt lake brine. The adsorption method has attracted much attention due to its advantages such as high selectivity, good separation effect, simple operation, no pollution, recyclable adsorbent and low cost.

[0003] Lithium adsorbents are mainly divided into inorganic adsorbents and organic adsorbents. Common inorganic lithium adsorbents include manganese-containing adsorbents, titanium-containing adsorbents, and aluminum-based adsorbents. The above adsorbents are currently very common as lithium adsorbents, but this type of adsorbent has disadvantages such as low adsorption capacity and high dissolution rate; organic adsorbents include a class of adsorbents represented by sulfonic acid groups, thiourea groups, crown ethers, chitosan, etc. Its binding mechanism includes Coulomb force adsorption, electrostatic attraction, complex coordination, ion exchange, etc. Although this type of adsorbent has a good adsorption effect, this type of adsorbent has poor selectivity and cannot achieve effective separation and recovery of metals. At the same time, due to the high monomer cost and complex synthesis path, its application in industrial lithium extraction is limited.

[0004] Powdered materials usually have a high specific surface area and abundant surface active groups, so their adsorption capacity is large and the adsorption rate is fast, but it is usually difficult to separate from water, and it is also easy to cause secondary pollution, and it is difficult to be directly used in the operation of industrial columns. Granular adsorbents are easy to prepare, functionalize, separate and regenerate, but their adsorption capacity is generally low and the adsorption rate is also slow. Nanofiber materials generally have a large specific surface area and high porosity, so their adsorption capacity is high and the adsorption rate is fast. At the same time, it is easy to separate or recycle after adsorption. Therefore, fiber materials are considered to be excellent adsorbents for heavy metals. CN118142504A discloses a method for targeted lithium extraction from lithium-containing wastewater by a polymer adsorbent containing diketones, and discloses a cellulose polymer adsorbent of β-diketones, but the adsorbent grafts diethylene ketone on the end of cellulose, needs to undergo multiple reactions and sedimentation, is difficult to synthesize, and is difficult to achieve mass production. Therefore, obtaining a good adsorbent material that can be prepared in large quantities is one of the key factors to solve the high selectivity and high adsorption capacity of lithium resources.

[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention

[0006] The first technical problem to be solved by the present invention is: a method for preparing a polyvinyl alcohol spun fiber adsorbent is proposed to solve the problems of poor structural selectivity, low adsorption capacity, poor stability, and inability to prepare in large quantities of existing adsorbents for adsorbing lithium ions.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a polyvinyl alcohol spinning fiber adsorbent comprises the following preparation steps:

[0009] S01: Dissolve polyvinyl alcohol in a solvent, stir at 60-80°C until completely dissolved to form a uniform polyvinyl alcohol solution; the solvent is N,N-dimethylformamide, and the mass ratio of the polyvinyl alcohol to the N,N-dimethylformamide is 1:20-30; at a higher temperature, the PVA molecular chains expand, and the solvent molecules penetrate between the molecular chains of the PVA to form a uniform solution. Too low a temperature will result in incomplete dissolution of the PVA, and too high a temperature may cause partial degradation of the PVA. The present invention maintains an appropriate stirring rate at 60-80°C to ensure that the PVA is evenly dispersed in DMF to form a stable solution.

[0010] S02: Add ethylenediamine to the polyvinyl alcohol solution in proportion, and continue stirring until completely mixed; heat the solution to 70°C and maintain for 4-6 hours to ensure that ethylenediamine and polyvinyl alcohol fully react; the addition ratio of ethylenediamine is controlled at 10%-20% of the mass of polyvinyl alcohol; the present invention accurately controls the amount of ethylenediamine to ensure sufficient reaction with PVA and avoid side reactions. The addition of ethylenediamine introduces amino groups into the PVA molecular chain, thereby enhancing the complexing ability of PVA for metal ions.

[0011] S03: Under stirring, slowly add diketone, keep the reaction temperature at 70°C, and continue stirring for 24-48 hours to form a modified polyvinyl alcohol solution containing diketone with enhanced adsorption performance; the dripping speed of the diketone is controlled in stages to ensure that the dripping time is controlled within 10 hours; when the dosage of polyvinyl alcohol is less than 100g, the dripping speed of diketone is controlled at 0.1-1mL / min; when the dosage of polyvinyl alcohol is between 100-1000g, the dripping speed of diketone is controlled at 1-10 mL / min; when the dosage of polyvinyl alcohol is greater than 1000g, the dripping speed of diketone is controlled at 10-50mL / min; to ensure that the speed is fast enough in large-scale production and the dripping time does not exceed 10 hours. Preferably, multiple dripping channels can be set according to actual conditions to avoid excessive local reaction and uneven reaction. The mass ratio of the polyvinyl alcohol to the diethylene ketone is 1:2; diethylene ketone acts as a crosslinking agent and reacts with the amino and hydroxyl groups on the PVA molecular chain to form a crosslinking structure. The formation of the crosslinking structure not only enhances the mechanical properties of the fiber, but also improves the durability and reusability of the adsorbent.

[0012] Polyvinyl alcohol (PVA) is a commonly used polymer material with good mechanical properties and biocompatibility. However, due to the lack of functional groups with strong adsorption capacity, the adsorption performance of lithium ions is weak. The present invention introduces amino groups by introducing other functional groups and copolymerizing with amino-containing compounds such as ethylenediamine. The amino groups can form more stable coordination bonds with lithium ions, thereby enhancing the capture ability of lithium ions on the surface of the adsorbent, thereby improving the adsorption capacity. Then, diethylene ketone is introduced for cross-linking to form a modified PVA solution with enhanced adsorption performance. The present invention controls the concentration of the modified polyvinyl alcohol to 5-20wt% by modifying the polyvinyl alcohol solution and controlling the mass ratio of polyvinyl alcohol, N,N-dimethylformamide, ethylenediamine and diethylene ketone to adapt to the preparation of electrospinning. By blending, high adsorption capacity and good mechanical properties can be achieved in the adsorbent at the same time. This composite material can not only efficiently adsorb lithium ions, but also maintain stability in multiple adsorption-desorption cycles.

[0013] S04: The modified polyvinyl alcohol solution after the reaction is cooled to room temperature, and formed into fibers by electrospinning technology, and then the formed fibers are placed in a curing bath, washed and dried after curing; a polyvinyl alcohol spinning fiber adsorbent with good structure and high adsorption performance is obtained. Electrospinning is a method of making ultrafine fibers from polymer solutions or melts through electrostatic force. Compared with traditional spinning technology, electrospinning can produce fibers with diameters ranging from nanometers to micrometers, with extremely high specific surface area and porosity, which is beneficial to improving the adsorption capacity of the adsorbent. The curing process is to change the surface chemical environment of the fiber to form a more stable three-dimensional network structure, which helps to improve the strength and chemical resistance of the fiber.

[0014] Furthermore, step S04 specifically includes:

[0015] S41: After the polyvinyl alcohol modification is completed, the reaction solution is cooled to room temperature;

[0016] S42: The reaction solution is loaded into a syringe and connected to an electrospinning device for electrospinning; during the electrospinning process, the voltage range is between 10 and 30 kV, and the spinning distance (needle and collector) is 10 to 20 cm. The flow rate of the syringe is between 0.1 and 1 mL / h.

[0017] S43: collecting the electrospun fibers and placing them in a curing bath for curing, wherein the temperature of the curing bath is controlled at -20 to 10°C;

[0018] S44: then repeatedly washing the solid material until the washing liquid is colorless and transparent, so as to remove the residual solvent and unreacted reagent;

[0019] S45: The washed solid material is dried in a vacuum drying oven at a temperature of 50-70°C until completely dried. Too high a temperature will cause fiber shrinkage or degradation, while too low a temperature will result in incomplete drying, affecting fiber properties. The present invention dries in a vacuum environment to avoid oxidation and impurity adsorption, thereby ensuring the stability of the sample.

[0020] The second technical problem to be solved by the present invention is: a method for targeted lithium extraction from lithium-containing wastewater using a polyvinyl alcohol spun fiber adsorbent prepared by the above method is proposed. Through multi-cycle adsorption and adsorption-desorption cycle verification, the long-term use performance and regeneration ability of the adsorbent can be evaluated to ensure its stability and economy in multiple uses.

[0021] In order to achieve the above object, the technical solution adopted by the present invention is:

[0022] A method for targeted extraction of lithium from lithium-containing wastewater, using the polyvinyl alcohol spinning fiber adsorbent prepared by the above method, comprising the following steps:

[0023] (1) The polyvinyl alcohol spinning fiber adsorbent is added to a lithium ion solution of a certain concentration, and adsorbed in a constant temperature oscillating shaker for 12 to 36 hours to complete the adsorption of lithium ions; during the lithium ion adsorption, the temperature of the constant temperature oscillating shaker is set to 25°C, and the speed of the constant temperature oscillating shaker is set to 180 rpm; the solubility of the lithium ion aqueous solution is 100 mg / L to 800 mg / L; the pH is 1 to 12; and the preferred pH is 5 to 9.

[0024] (2) Then, the lithium-containing polyvinyl alcohol spun fiber adsorbent is added to a certain concentration of hydrochloric acid and desorbed on a constant temperature oscillating shaker for 6 to 24 hours to complete the desorption of lithium ions; during desorption, the solubility of the hydrochloric acid solution is 0.1 mol / L.

[0025] (3) After desorption, the adsorbent is washed with deionized water several times to remove residual hydrochloric acid, and then dried to restore its adsorption performance;

[0026] Preferably, the present invention repeats the above steps 1 to 3.

[0027] In order to increase the number of cycles, during continuous cyclic adsorption, the pH of the lithium ion solution changes in the manner of "weak acid-neutral-weak alkaline-neutral-weak acid", and the same batch of adsorbents is recycled multiple times, and desorption and regeneration are performed after each adsorption. The present invention operates under neutral to weakly alkaline conditions, and the milder pH range can reduce the chemical degradation of the adsorbent, while the pH changes during the adsorption and desorption process can promote the release and re-adsorption of lithium ions. By switching the pH in the manner of "weakly acidic-neutral-weakly alkaline-neutral-weakly acidic", the destructive effects of extreme acidic or alkaline conditions on the adsorbent can be reduced, which may help extend the cycle life of the adsorbent. The milder pH changes can reduce chemical damage to the adsorbent material while maintaining the high efficiency of the adsorbent in multiple cycles. It helps to enhance the long-term stability and service life of the adsorbent.

[0028] After each cycle, the adsorption capacity and desorption efficiency of the adsorbent are recorded to monitor its performance changes. By comparing the adsorption capacity and desorption efficiency under different numbers of cycles, the performance attenuation of the adsorbent after multiple uses is analyzed. The regeneration capacity of the adsorbent is evaluated, the number of times it can be used sustainably is determined, and the economic efficiency of the adsorbent is analyzed. Based on the experimental data, suitable mathematical models (such as Langmuir model, kinetic model, etc.) are used for data fitting to analyze the kinetic behavior of adsorption and desorption. An adsorption-desorption cycle model is established to simulate and predict the performance of the adsorbent under different operating conditions, and to optimize the preparation formula and operating process of the adsorbent. According to the results of the adsorption-desorption cycle verification, the adsorbent formula or operating parameters, such as the pH value, flow rate, temperature, etc. of the solution, are adjusted to further improve the performance and durability of the adsorbent.

[0029] The beneficial effects of the present invention are:

[0030] (1) The present invention modifies polyvinyl alcohol by using ethylenediamine and diethylene ketone, and then obtains polyvinyl alcohol spinning fibers by electrospinning. The addition of ethylenediamine introduces amino groups into the PVA molecular chain, thereby enhancing the chelating ability of PVA for metal ions. The hydrogen bonding between the amino group and the hydroxyl group, diethylene ketone as a cross-linking agent, reacts with the amino group and hydroxyl group on the PVA molecular chain to form a cross-linked structure. The formation of the cross-linked structure not only enhances the mechanical properties of the fiber, but also improves the durability and reusability of the adsorbent. As a result, the polyvinyl alcohol spinning fibers have diketone functional groups, and the carbonyl group on the diketone can form a relatively stable chelate structure with lithium ions, thereby being able to extract lithium ions from wastewater and achieve selective recovery of lithium ions;

[0031] (2) The preparation method of the polyvinyl alcohol spun fiber adsorbent material prepared by the electrospinning technology of the present invention is simple to operate, has a simple process and low cost. It is suitable for water treatment, heavy metal removal, gas purification and other fields, especially scenarios requiring high adsorption capacity and rapid response. Electrospinning is a technology that can produce fibers on a large scale. By adjusting the process parameters, it can achieve kilogram-level or even larger-scale material preparation, which is suitable for industrial applications. For the recovery of lithium resources in complex lithium-containing wastewater, the maximum adsorption capacity of lithium ions in water is 29.2 mg / g, which can achieve the selective separation of lithium ions from a mixed solution of five metal ions such as nickel, cobalt, manganese, magnesium and calcium. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 This is a SEM image of the polyvinyl alcohol spun fiber adsorbent prepared by the present invention;

[0034] Figure 2 The isothermal adsorption curves of the polyvinyl alcohol spinning fiber adsorbent before and after grafting with different proportions of diketene are compared in the present invention;

[0035] Figure 3 This is a graph showing the adsorption capacity of polyvinyl alcohol spun fiber adsorbent for lithium ions at different pH values ​​of the present invention;

[0036] Figure 4 This is a graph showing the selective adsorption capacity of the polyvinyl alcohol spun fiber adsorbent of the present invention for lithium ions;

[0037] Figure 5 The graph shows the cycling performance of the polyvinyl alcohol spun fiber adsorbent for lithium ions and the regeneration of the material. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0040] A method for preparing a polyvinyl alcohol spinning fiber adsorbent comprises the following preparation steps:

[0041] S01: dissolving polyvinyl alcohol in a solvent, stirring at 60-80° C. until completely dissolved, to form a uniform polyvinyl alcohol solution; the solvent is N,N-dimethylformamide, and the mass ratio of the polyvinyl alcohol to the N,N-dimethylformamide is 1:20-30;

[0042] S02: Add ethylenediamine to the polyvinyl alcohol solution in proportion and continue stirring until completely mixed; heat the solution to 70°C and maintain for 4-6 hours to ensure that ethylenediamine and polyvinyl alcohol fully react; the addition ratio of ethylenediamine is controlled at 10%-20% of the mass of polyvinyl alcohol;

[0043] S03: under stirring, adding diketene dropwise, maintaining the reaction temperature at 70°C, and continuing stirring for 24-48 hours to form a modified polyvinyl alcohol solution containing diketone with enhanced adsorption performance; the mass ratio of the polyvinyl alcohol to the diketene is 1:2;

[0044] S04: After the polyvinyl alcohol modification is completed, the reaction solution is cooled to room temperature; the reaction solution is loaded into a syringe and connected to the electrospinning equipment for electrospinning; during the electrospinning process, the number of syringes is changed as the raw materials increase, the voltage range is between 10~30 kV, and the spinning distance is 10~20 cm. The flow rate of the syringe is between 0.1~1mL / h. The fibers obtained by electrospinning are collected and placed in a curing bath for curing treatment, and the temperature of the curing bath is controlled at -20~10℃; then the solid material is repeatedly washed until the washing liquid is colorless and transparent to remove residual solvents and unreacted reagents; the washed solid material is dried in a vacuum drying oven, and the temperature is controlled between 50~70℃ until it is completely dry.

[0045] The invention can realize the preparation of kilogram-level polyvinyl alcohol spinning fiber adsorbent, and the reaction conditions are mild and easy to control, which helps to reduce energy consumption and equipment requirements, thereby making it easier to realize industrial production. The solvent of polyvinyl alcohol is N,N-dimethylformamide, which has good solubility and reactivity and helps to simplify the process and is suitable for large-scale operation.

[0046] Specifically, the materials and equipment include:

[0047] Polyvinyl alcohol (PVA): Industrial grade PVA powder, molecular weight 88,000~98,000 Da.

[0048] N,N-Dimethylformamide (DMF): Industrial grade solvent.

[0049] Ethylenediamine (EDA): Industrial grade purity.

[0050] Divinyl Ketone: Industrial grade purity.

[0051] Electrospinning equipment: Industrial-grade electrospinning device with large-capacity syringe and high-voltage power supply.

[0052] A method for preparing a polyvinyl alcohol spinning fiber adsorbent comprises the following preparation steps:

[0053] S01: Dissolve 1 kg of polyvinyl alcohol in a solvent, and stir at 75°C until it is completely dissolved to form a uniform polyvinyl alcohol solution; the solvent is N,N-dimethylformamide, and the mass ratio of the polyvinyl alcohol to the N,N-dimethylformamide is 1:20; the obtained solution is tested for uniformity in a static state to ensure that there is no clot or precipitation.

[0054] S02: Add 100g of ethylenediamine to the polyvinyl alcohol solution in proportion and continue stirring until completely mixed; heat the solution to 70°C and maintain for 6 hours, and take samples regularly for pH value testing to confirm the uniform dispersion and sufficient reaction of ethylenediamine.

[0055] S03: Under stirring, slowly add 2kg of diethylene ketone, keep the reaction temperature at 70°C, and continue stirring for 24-48h to form a modified polyvinyl alcohol solution with enhanced adsorption performance; the dripping speed of the diethylene ketone is controlled at 10mL / min; avoid excessive local reaction to cause uneven reaction. After the reaction, test the viscosity and uniformity of the solution.

[0056] S04: After the modification of polyvinyl alcohol is completed, the reaction solution is cooled to room temperature; the reaction solution is loaded into a syringe and connected to an electrospinning device for electrospinning; during the electrospinning process, the voltage range is between 25 kV and the spinning distance (needle and collector) is 15 cm. The flow rate of the syringe is between 0.5 mL / h. The fibers obtained by electrospinning are collected and placed in a curing bath for curing treatment, and the temperature of the curing bath is controlled at -10°C; then the solid material is repeatedly washed until the washing liquid is colorless and transparent to remove residual solvents and unreacted reagents; the washed solid material is dried in a vacuum drying oven, and the temperature is controlled between 60°C until it is completely dried. The final dry fiber mass is 1.25kg. The process of the present invention is stable, repeatable, safe to operate, and the equipment load is within a controllable range, indicating that this technical route has the potential for large-scale industrial production.

[0057] Adsorption-desorption performance verification

[0058] A method for targeted extraction of lithium from lithium-containing wastewater, using the polyvinyl alcohol spinning fiber adsorbent prepared by the above method, comprising the following steps:

[0059] (1) The polyvinyl alcohol spinning fiber adsorbent is added to a lithium ion solution of a certain concentration, and adsorbed in a constant temperature oscillating shaker for 24 hours to complete the adsorption of lithium ions; during the lithium ion adsorption, the temperature of the constant temperature oscillating shaker is set to 25°C, and the speed of the constant temperature oscillating shaker is set to 180rpm. Increasing the contact degree between the polyvinyl alcohol spinning fiber material and the lithium solution can improve the binding efficiency between the polyvinyl alcohol spinning fiber and the lithium ions, thereby adsorbing the lithium ions in the lithium ion solution. The solubility of the lithium ion aqueous solution is 500mg / L; the pH is 5-9.

[0060] (2) Then, the lithium-containing polyvinyl alcohol spun fiber adsorbent is added to 0.1 mol / L hydrochloric acid and desorbed on a constant temperature shaking table for 6 hours to complete the desorption of lithium ions;

[0061] (3) After desorption, the adsorbent is washed with deionized water several times to remove residual hydrochloric acid, and then dried to restore its adsorption performance;

[0062] Preferably, the present invention repeats the above steps 1 to 3. The same batch of adsorbent is recycled for multiple times, and desorption and regeneration are performed after each adsorption.

[0063] Figure 1 This is a scanning electron microscope image of polyvinyl alcohol spun fiber adsorbent material. Figure 1 It can be seen that the fiber surface is rough and there are a large number of grafted substances on the surface, which also proves that the synthesis of the material is successful. It can also be seen that the fiber has a large surface area and there are many exposed adsorption sites on the surface, which is conducive to adsorption.

[0064] Polyvinyl alcohol spun fiber adsorbent material was used to adsorb lithium ion aqueous solutions of different concentrations to illustrate the effect of adsorbent raw materials on lithium ion adsorption:

[0065] Test method:

[0066] (1) First, prepare lithium nitrate aqueous solutions with lithium ion concentrations of 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 700 mg / L and 800 mg / L respectively; then take 20 mL of the solutions of these concentrations into 8 50 mL conical flasks respectively;

[0067] (2) Weigh 8 portions of polyvinyl alcohol spun fiber adsorbent material (20 mg) using a 1 / 10,000 electronic balance, add the weighed materials into conical flasks containing lithium ion aqueous solutions of different concentrations, and place them in a constant temperature oscillator with pre-set parameters of temperature 25°C, rotation speed 180 rpm, and time 24 h for adsorption experiment;

[0068] (3) Using an atomic absorption spectrometer (AAS) to measure the lithium ion concentration in the ion solution before and after adsorption in the conical flask;

[0069] (4) Repeat the above steps (1) to (3), except that the ratios of ethylenediamine, diethylene ketone, and polyvinyl alcohol in the polyvinyl alcohol spun fiber adsorbent material prepared in step (2) are 0.1:1:2; 0.2:1:1; 0.2:3:2; and 0.1:2:1, respectively.

[0070] Figure 2 The above isothermal adsorption curve is fitted to show that the adsorption capacity of the polyvinyl alcohol spun fiber adsorption material for lithium ions is 13.8 mg / g, 18.5 mg / g, 20 mg / g, and 28.1 mg / g, respectively, indicating that the higher the content of diketone in the polyvinyl alcohol spun fiber adsorption material, the greater the adsorption capacity, and the best effect is achieved when the dosage of ethylenediamine is 10% of polyvinyl alcohol.

[0071] Polyvinyl alcohol spun fiber adsorbent material was used to adsorb lithium ion aqueous solutions with different pH values ​​to illustrate the effect of pH on lithium ion adsorption:

[0072] Test method:

[0073] (1) First, prepare 100 mL of lithium nitrate aqueous solution with a lithium ion concentration of 500 mg / L at pH 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12 respectively, and measure 20 mL of the lithium ion solution with different pH values ​​using a 25 mL graduated cylinder and place it in 12 50 mL conical flasks;

[0074] (2) Weigh 20 mg of 12 portions of the polyvinyl alcohol spun fiber adsorption material in Example 1, and put the weighed materials into 50 mL conical flasks containing 500 mg / L lithium at pH 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, and 12, respectively, and put them into a constant temperature oscillator with the parameters set in advance as temperature 25°C, rotation speed 180 rpm, and time 24 h for adsorption experiment;

[0075] (3) Take the ion concentrations before and after adsorption in the conical flask respectively, and use atomic absorption spectrometry (AAS) to measure the lithium ion concentration in the solution.

[0076] Figure 3 The figure shows the adsorption capacity of polyvinyl alcohol spun fiber adsorbent for lithium ions at different pH values. The results show that the polyvinyl alcohol spun fiber adsorbent has the best adsorption effect on lithium ions in an aqueous solution with a pH of 8, with an adsorption capacity of 29.2 mg / g. At the same time, it can be seen that the adsorption capacity is slightly different when the pH is 6 and 7.

[0077] The adsorption selectivity of lithium ions was determined using polyvinyl alcohol spun fiber adsorbent material:

[0078] Test method:

[0079] (1) A mixed solution containing 50 m mol / L lithium ions, 50 m mol / L nickel ions, 50 m mol / L cobalt ions, 50 m mol / L manganese ions, 50 m mol / L magnesium ions, and 50 m mol / L calcium ions is prepared, with a volume of 20 mL, for a total of 2 portions; and then the mixed solution is added to two 50 mL conical flasks respectively;

[0080] (2) Weigh 20 mg of the polyvinyl alcohol spun fiber adsorbent material in Example 1, a total of 2 portions, and put them into a pre-prepared mixed solution containing 50 m mol / L lithium ions, 50 m mol / L nickel ions, 50 m mol / L cobalt ions, 50 m mol / L manganese ions, 50 m mol / L magnesium ions, and 50 m mol / L calcium ions, and put them into a constant temperature oscillator with pre-set parameters of temperature 25°C, rotation speed 180 rpm, and time 24 h for adsorption experiment;

[0081] (3) The mixed ion solutions before and after adsorption in the conical flask were taken separately, and the concentrations of lithium ions, nickel ions, cobalt ions, manganese ions, magnesium ions and calcium ions in the solutions were determined using an inductively coupled plasma mass spectrometer (ICP-MS).

[0082] Figure 4 The selective adsorption capacity of the polyvinyl alcohol spun fiber adsorbent material for lithium ions shows that the polyvinyl alcohol spun fiber adsorbent material can separate lithium ions from a mixed solution containing nickel ions, cobalt ions, manganese ions, calcium ions and magnesium ions, indicating that the polyvinyl alcohol spun fiber adsorbent material also has the potential to separate and recover lithium elements in complex lithium-containing wastewater.

[0083] Figure 5 As for the cycling performance of the polyvinyl alcohol spun fiber adsorbent material for lithium ions and the regeneration of the material, the adsorption capacity of the polyvinyl alcohol spun fiber adsorbent material can reach 23.2 mg / g after 5 cycles of lithium adsorption, which is 20.5% lower than the maximum adsorption capacity. However, the material loss rate of the adsorbent material is only 10% after 5 cycles. The spinnable fiber material as an adsorbent has outstanding material stability and has great potential in industrial production.

[0084] Therefore, the synthesized polyvinyl alcohol spinning fiber adsorption material has a high adsorption activity under alkaline conditions, and the adsorption capacity of lithium ions can reach up to 29.2 mg / g, which is 3.5 to 7.2 times that of general commercial resin adsorbents. The polyvinyl alcohol spinning fiber adsorption material can selectively separate and recover lithium ions from a mixed solution of lithium, nickel, cobalt, manganese, calcium, magnesium and other ions.

[0085] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a polyvinyl alcohol spinning fiber adsorbent, characterized in that: The steps are as follows: S01: dissolving polyvinyl alcohol in a solvent, stirring at 60-80°C until it is completely dissolved to form a uniform polyvinyl alcohol solution; S02: Add ethylenediamine to the polyvinyl alcohol solution at a rate of 10% to 20% of the mass of the polyvinyl alcohol, and continue stirring until completely mixed; heat the solution to 70°C and maintain for 4 to 6 hours to ensure that ethylenediamine and polyvinyl alcohol fully react; S03: Slowly add diketone under stirring, keep the reaction temperature at 70°C, and continue stirring for 24-48 hours to form a modified polyvinyl alcohol solution containing diketone with enhanced adsorption performance; the concentration of the modified polyvinyl alcohol is 5-20wt%; S04: cooling the modified polyvinyl alcohol solution after the reaction to room temperature, and forming it into fibers by electrospinning technology, and then placing the formed fibers in a curing bath, and then washing and drying them after curing; The polyvinyl alcohol spun fiber adsorbent with good structure and high adsorption performance is obtained.

2. The method for preparing a polyvinyl alcohol spun fiber adsorbent according to claim 1, characterized in that: In step S01, the solvent is N,N-dimethylformamide, and the mass ratio of the polyvinyl alcohol to the N,N-dimethylformamide is 1:20-30.

3. The method for preparing a polyvinyl alcohol spinning fiber adsorbent according to claim 1, characterized in that: In step S03, the mass ratio of the polyvinyl alcohol to the diketene is 1:

2.

4. The method for preparing a polyvinyl alcohol spinning fiber adsorbent according to claim 1, characterized in that: In step S03, the dripping speed of diketene is controlled in stages to ensure that the dripping time is controlled within 10 hours.

5. The method for preparing a polyvinyl alcohol spinning fiber adsorbent according to claim 1, characterized in that: Step S04 specifically includes: S41: After the polyvinyl alcohol modification is completed, the reaction solution is cooled to room temperature; S42: loading the reaction solution into a syringe, and connecting the syringe to an electrospinning device for electrospinning; S43: collecting the electrospun fibers and placing them in a curing bath for curing, wherein the temperature of the curing bath is controlled at -20 to 10°C; S44: then repeatedly washing the solid material until the washing liquid is colorless and transparent, so as to remove the residual solvent and unreacted reagent; S45: The washed solid material is dried in a vacuum drying oven at a temperature controlled between 50 and 70°C until completely dried.

6. The method for preparing a polyvinyl alcohol spinning fiber adsorbent according to claim 5, characterized in that: In step S42, during the electrospinning process, the voltage range is between 10 and 30 kV, the spinning distance is between 10 and 20 cm, and the flow rate of the syringe is between 0.1 and 1 mL / h.

7. A method for targeted extraction of lithium from lithium-containing wastewater, using a polyvinyl alcohol spinning fiber adsorbent prepared by the method according to any one of claims 1 to 6, characterized in that: The following steps are involved: (1) adding the polyvinyl alcohol spinning fiber adsorbent to a lithium ion solution of a certain concentration, and adsorbing the lithium ions in a constant temperature shaking table for 12 to 36 hours, thereby completing the adsorption of lithium ions; (2) Then, the lithium-containing polyvinyl alcohol spun fiber adsorbent is added to a certain concentration of hydrochloric acid and desorbed on a constant temperature shaking table for 6 to 24 hours to complete the desorption of lithium ions; (3) After desorption, the adsorbent is washed with deionized water several times to remove residual hydrochloric acid, and then dried to restore its adsorption performance; Repeat the above steps (1) to (3).

8. A method for targeted lithium extraction from lithium-containing wastewater according to claim 7, characterized in that: In step (1), the temperature of the constant temperature oscillating shaker is set to 25° C., the speed of the constant temperature oscillating shaker is set to 180 rpm; the solubility of the lithium ion aqueous solution is 100 mg / L~800 mg / L; and the pH is 5~9.

9. A method for targeted lithium extraction from lithium-containing wastewater according to claim 7, characterized in that: In step (2), the concentration of the hydrochloric acid solution is 0.1 mol / L.

Citation Information

Patent Citations

  • Method for targeted extraction of lithium from lithium-containing wastewater by using diketone-containing polymer adsorbent

    CN118142504A

  • Nanometer fibrous lithium ion sieve adsorption film as well as preparation method and application thereof

    CN119075900A